Tropical forage-based systems to mitigate greenhouse gas emissions - Peters, Michael; Rao, Idupulapati M.; Fisher, M.; Subbaraoa, Guntur V.; Martens, S.; Herrero, Mario; Hoek, Rein van der; Schultze-Kraft, Rainer; Miles, John W.; Castro, A.; Graefe, Sophie; Tiemann, Tassilo T.; et al. (International Center for Tropical Agriculture, 2012)
Agriculture and livestock production are major contributors to greenhouse gas emissions. Foragebased systems dominate much of agriculture in the tropics, providing livelihoods to farmers but also affecting local and global environments. In this paper, we attempt to answer the question, how can farmers and livestock keepers improve their livelihoods while reducing negative impacts on the environment? We focus on forage-based systems in the tropics, emphasizing smallholders and the role of forages. In particular, we address the potential of tropical forage-based systems not only to contribute to reducing greenhouse gas emissions but also to sequester carbon in soil in substantial amounts to mitigate climate change. We also discuss the associated benefits of forage-based systems to enhancing the eco-efficiency of farming in the tropics and to improving rural livelihoods. We identify opportunities in forage-based systems that are economically sustainable and socially equitable with the lowest possible ecological footprint. With the global community increasingly aware of the environmental implications of agriculture, forage-based systems should figure prominently as “LivestockPlus” (meat, milk, and more) options in future innovative agricultural systems. We hope that this paper will stimulate discussion that leads to further investment from donors in research on improving the eco-efficiency of forage-based systems in the tropics.